O processo de institucionalização do curso de administração a distância da UFRN - Novais, Sueli Menelau de (2009)
This work aims to describe how is occurring through the process of institutionalizing the Administration distance course of UFRN. To this end, structured into two parts: through research and analysis of content, sought to impound as if gave historic process of creation, as well as identify variables isomórficas, proposed by Powell and DiMaggio (1991), on the actions undertaken, and still present, institutional actors-having been found three typologies; then investigated the process itself, analyzing the factors of institutionalization suggested Esman (1966-1972), internal structure doctrine, leadership programme, resources, links and exchanges, from the political plan educational course. As the research methodology was defined as qualitative, even though I used survey to collect, reviewed the second ANOVA. The results found in this step pointed out that only the doctrine and internal structure variables are consistent with the assumptions of model; we found for other, discharged indicated a gap between the political acts contemplated in teaching and the actions taken so far, unfavourable element to its legitimacy. However, although the implications found in the analysis of these factors suggest that this course can derive one more discontinuous Government proposal of distance course, this study believes that are still reasonable assistance to facilitate and promote the process aimed at strengthening the progress achieved so far in the success of its institutionalization